Dynamical Behavior of Some Recursive Exponential Difference Equations - Khaliq, Abdul; Shabbir, Muhammad; Zubair, Muhammad; Rohail, Muhammad; Sadiq, Stephen (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study boundedness, persistence and rate of convergence of system of difference equations of exponential form $r_{n+1}=\frac{λ +e^{-(μ r_{n}+ξ s_{n})}}{δ +μ r_{n}+ξ s_{n}}, \ s_{n+1}=\frac{λ +e^{-(μ s_{n}+ξ t_{n})}}{δ +μ s_{n}+ξ t_{n}}, \ t_{n+1}=\frac{λ +e^{-(μ t_{n}+ξ r_{n})}}{δ +μ t_{n}+ξ r_{n}},$ where $n=0, 1, 2,…$ and $λ $, $μ $, $ξ $ and $δ $ are non-negative constants and the initial conditions $r_{0}$, $s_{0}$, $t_{0}$ are non-negative real values.